The Role of Ukrainian Universities in Creating Technology Incubators (Journal of Information Technologies in Education (ITE), 2008)
This paper examines the opportunities for economic growth and business development from university-based incubators. Universities are shown to be excellent sources of technical and business management assistance for start-up businesses in the incubator and national policies are recommended to support the establishment of incubators at Ukrainian universities.